Relationship between Principal Supervision, Work Culture, and Work Motivation with the Performance of Elementary Teachers in Sector 2, Binjai Utara District - Lies Eka Mardhani; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics University, 2023)
This study aimed to determine: (1) the relationship between the supervising principal with teacher performance; (2) the relationship between work culture with the performance of teachers; (3) the relationship between work motivation with teacher performance; and (4) the relationship between the supervision of the principal, work culture and work motivation with teacher performance. Subjects were private elementary school teachers in Sector 2, Binjai Utara District with a total sample of 60 peoples. Sampling was done by random sampling proportional. Based on hypothesis testing can be concluded: (1) there is a significant relationship between the principal supervision of teacher performance ry1.23 = 0.36 > rtable = 0.17 and tobserve = 6.12 > ttable = 1.65; (2) there is a significant relationship between teachers' work culture with the performance of ry2.13 = 0.21 > rtable = 0.17 and tobserve = 2.88 > ttable = 1.65’; (3) there is a significant relationship between work motivation with teacher performance by ry3.12 = 0.30 > rtable = 0.17 and tobserve = 4.59 > ttable = 1.65; and (4) there is a significant relationship between the principal supervision, cultural work, and motivation to work with teacher performance by Ry(123) = 0.50 > rtable = 0.17 and Fobserve = 13.50 > Ftable = 2.65. The results obtained by the principal supervision, work culture, and motivation to work together to contribute 25% of the performance of teachers, and the rest are other circumstances determined.